The Impact of Islamic Methodology of Sustainability and Circular Economy - El-Hussein, Omer Mahgoub (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to explore the circular economy and sustainability, and shed light on Islam’s values and concepts that encourage people not to waste resources and take a moderate way of living on earth. Also, this study looks at to what extent that Islam connected its values to the concepts of circular, sustainable economy and the preservation of the environment as principles that had introduced very early prior to the establishment of the concept of the circular economy. Furthermore, the study aims to explore the circular economy from the perspective of the concept of entrepreneur and sustainability. The purpose of the study achieves the study purpose, the author uses an analytical, descriptive methodology to obtain the necessary results about how Islam’s values are connected to sustainability, and how those values are the main drive for the circular economy, sustainability and environment protection. Finally, the most prominent outcome of this study is that Islam’s values of ethics, moderation, forbidden of wasting resources and flourishing the earth all are considered a substantial principle of circular economy, protecting environment and fulfilling sustainability. It’s believed that the capitalist economy is unlikely able to address sustainability successfully without taking the necessary values and ethics into consideration. Contrarily, capitalist economy contradicts sustainability principles and the environment protection and, necessarily, the circular economy. Therefore, it is believed that countries will face alone difficult to reap the benefits of its vision of sustainability and the circular economy unless the entire region adopts a development strategy that relies on sustainability, and environmental protection to fulfill the circular economy principles.